Smart Card Analysis: Malaysian Perspectives - Mohd Hatta, Kasuma Nurhazwani (2009)
In this research paper, the smart card will be widely explored and be exposed to make them known and become part of human lives without any doubt. Smart card is a way of living and thus, the adaptability is hopefully to become a bliss for the user and not the other way round.